STUDY OF ATTITUDES TOWARDS THE USE OF MOBILE PHONES WHILE DRIVING WITH IMPLICIT ASSOCIATION TESTS AND SELF-ASSESSMENT PROCEDURES - Vinogradova, Zhanna; Plotka, Irina; Smirnova, Iveta; Blumenau, Nina; Igonin, Dmitry (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Analysis of studies shows that in studying attitudes towards risky and safe driving only few researches are based on the use of implicit methods. The aim of the study: the study of attitudes towards the use of mobile phones while driving with the use of Implicit Association Tests and self-assessment procedures. Participants: 69, age 21-59, M = 42, SD = 9.02, 27 female and 42 male, all with B category driver licenses, driving experience 9-24 years. Implicit measurements: two experimental procedures of the Implicit Association Test (IAT) developed by the authors for measuring attitudes towards the use of mobile phones while driving: IAT and self-concept IAT Explicit measurements: a self-assessment procedure developed by the authors "Scale of measuring attitudes towards the use of mobile phones while driving," cross-cultural Personality Questionnaire ZKPQ-50-CC (Aluja, Rossier, García, Angleitner, Kuhlman, & Zuckerman, 2006). A positive relationship between the results of measurements using IAT and self-concept IAT was found in participants with high anxiety. The effect size obtained with the IAT is larger than the effect size obtained with self-concept IAT. A relationship between the results of measurement of attitudes towards the use a mobile phone while driving, measured by experimental procedures and the personal factors was found.